Bayesian methods for classification inappropriate web pages - Rodríguez R, Jorge E.; Ortiz Pimiento, Jenny Paola (Visión electrónica, 2017)
The incursion of the Internet has created new forms of information and communication, but it can also carry great dangers, when its use is related to inappropriate content, such as, access to harmful contents and the rise of new kinds of crimes. In this situation, automatic filtering systems identify improper Internet content. This paper describes the use of an algorithm, to automatically filter out inappropriate Web pages. To accomplish this (automatic filtering) task implementation method TAN (Tree Augmented Naive Bayes) is plasma. Data mining algorithms and computational learning for the extraction process, representation and classification of web pages are implemented.